Conscious Motivations of Adolescent Visual Artists and Creative Writers: Similarities and Differences. Issue 4 (2nd October 2017) - Harrington, David M.; Chin-Newman, Christina S.
Abstract : This exploratory study was designed to expand the field's understanding of talented adolescent visual artists and creative writers and their conscious motivations for engaging in these creative activities. Accordingly, 233 talented high school visual arts ( n = 151) and creative writing ( n = 82) students were asked to rate the degree to which they believed their creative activities were motivated by each of a wide range of possible motivations. The students in both fields reported being very strongly motivated by the opportunities their activities provided them to use their imaginations, feel free, sense that they were being their "true" selves, regulate their emotions, capture moments in time, deepen their self-understanding, express themselves, improve their skills, and enhance their self-esteem. Some of these motivations correspond closely to those highlighted by theories of intrinsic motivation, competence motivation, and self-actualization, several are similar to those which have been reported by professional artists and writers, and some suggest that the students may have derived important psychological benefits from their creative activities. Theoretically plausible differences between the motivational profiles of the visual and creative writing students were identified and discussed.